A Toner Formula Based on Piper Betle Leaf Extract (Piper betle L.) to Control Excess Oil on Acne-Prone Skin - Rohmah, Aini Nur; Ambarwati, Neneng Siti Silfi; Jubaedah, Lilis (Jurnal Biologi Tropis, 2026)
Oily and acne-prone skin are common skin problems caused by excess sebum production by the sebaceous glands. Betel leaves (Piper betle L.) contain bioactive compounds such as tannins, flavonoids, phenols, and hydroxychavicol, which have the potential to help control sebum levels through astringent, antioxidant, and antibacterial activities. This study aimed to formulate a betel leaf extract toner, determine the physical characteristics of the preparation, and analyze its effectiveness in reducing sebum levels in acne-prone facial skin. This experimental study used two formulas: Formula 1 (F1) with a 3% extract concentration and Formula 2 (F2) with a 5% concentration. These formulas were tested on 20 respondents (10 per group) for seven days. Evaluation included organoleptic tests, homogeneity, pH, viscosity, irritation, and sebum level measurements using a skin analyzer before and after treatment. Data were analyzed using the Shapiro-Wilk test, Paired Sample t-test, Wilcoxon Signed Ranks Test, and Mann-Whitney U-test. The results showed that both formulas were homogeneous, non-irritating, and had pH (4.91 and 5.16) and viscosity (46.41 and 47.10 cPs) that met the standards for topical preparations. Formula 1 experienced a significant decrease in sebum levels from 51.00 to 45.40 (p = 0.005), while Formula 2 decreased from 51.20 to 48.70 (p = 0.011). However, the Mann-Whitney test showed no significant difference in effectiveness between the two concentrations (p = 0.102). It can be concluded that betel leaf extract toner at concentrations of 3% and 5% is effective in reducing sebum levels, but increasing the extract concentration does not provide a statistically significant difference in effectiveness.